Determination of Optimum Effective Range of Distribution Power Network with Due Account of Consumer Electric Supply Reliability - V. I. Rusan; O. Yu. Pukhalskaya (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers a problem pertaining to determination of  an optimum effective range of a distribution power network with due account of such factors as time, cost diversity and consumer electric supply reliability. Influence of these factors on an optimum effective range value of  the 10 кV electric network is investigated in the paper.